2006
DOI: 10.1590/s1519-69842006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Calliphoridae (Diptera) in Brazil's Tinguá Biological Reserve

Abstract: ABSTRACTthe Calliphoridae are flies of great ecological, medical and sanitary importance because they are decomposers of organic matter, mechanical vectors of pathogenic agents, and causers of myiasis. this paper attempts to ascertain the diversity of Calliphoridae in the tinguá Biological reserve and correlate meteorological data (temperature, relative humidity of the air, and precipitation) with the occurrence of these flies. the study was conducted at a site in the tinguá Biological reserve, located in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
4
20
0
Order By: Relevance
“…This sex bias was also observed by Paraluppi and Castellón (1994), Marinho et al (2006) andFerraz et al (2010a), and according to Sousa et al (2010), may also be related to the position of the trap, suspended 1.5m above the ground. The collecting of February 2010 resulted in the greatest numbers of specimens ( Figure 2).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This sex bias was also observed by Paraluppi and Castellón (1994), Marinho et al (2006) andFerraz et al (2010a), and according to Sousa et al (2010), may also be related to the position of the trap, suspended 1.5m above the ground. The collecting of February 2010 resulted in the greatest numbers of specimens ( Figure 2).…”
Section: Resultssupporting
confidence: 79%
“…Studies on the diversity of Calliphoridae in protected areas of the state of Rio de Janeiro are restricted to the Reserva Biológica do Tinguá (hereinafter referred to as REBIO Tinguá) (Marinho et al, 2006;Mello et al, 2007;Ferraz et al, 2010b). For the PARNA Tijuca, only the publication by D'Almeida and Lopes (1983), which focused on synanthropic flies, is available.…”
Section: Introductionmentioning
confidence: 99%
“…While twenty-six species were collected in this study, Mello et al (2007) and Marinho et al (2006), in other locations of the same Reserve, captured 13 and 10 species, respectively. All the species collected by these two authors were also cited in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Human effects in the Reserva Biológica do Tinguá have previously been reported by Marinho et al (2006), and this analysis drew attention to the need for further studies in the area. The parameters of interest include an estimation of forest conservation and human effect on dipterans in the Calliphoridae family; predominance and diversity of species on the edge and forest interior; better understanding of population dynamics; current dispersion of exotic species; identification of bioindicator species and, of paramount importance, in order to support preservation and conservation of the Atlantic Forest.…”
Section: Introductionmentioning
confidence: 87%
“…After the introduction of the exotic C. megacephala in Brazil, C. macellaria, usually very common in urban and rural areas, has become rare in these environments (Baumgartner and Greenberg 1885, Guimarães et al 1978, Marinho et al 2003, 2006. Several studies suggested that the decline was due to the competition during the larval stages (Aguiar-Coelho and Milward-deAzevedo 1996, Faria et al 1999, Andrade et al 2002.…”
mentioning
confidence: 99%